Short Communication: Infraspecific variations in essential oil compositions of Nepeta fissa from Iran - SEYED MEHDI TALEBI; MAJID GHORBANI NOHOOJI; MAHBOOBEH YARMOHAMMADI (Smujo International, 2017)
Talebi SM, Nohooji MG,Yarmohammadi M. 2017. Short Communication: Infraspecific variations in essential oil compositions of Nepeta fissa from Iran. Nusantara Bioscience 9: 318-321. Nepeta fissa C.A. Mey. is a member of Mint family (Lamiaceae) and distributed naturally in different regions of Iran. The aim of this investigation was to provide more information about the influence of environmental conditions on the essential oil composition of two populations, Polor and Dizin, of this species. The dry plant samples were submitted to hydrodistillation for 2.5 h, using a Clevenger-type apparatus. The highest amount of essential oil yields (0.2%) were obtained for Dizin population. Forty-nine compounds, representing 85.9 to 97.80% of the total essential oils, were separated and identified. In Dizin and Polor populations, the essential oils were characterized by the very high percentage of oxygenated monoterpenes (79.1%), oxygenated diterpenes (20.01%) that constituted the predominant classes, respectively. From the analyzed populations, the major compounds in Dizin population were 1, 8-Cineole, 4 a-Î±, 7-Î±, 7 a-Î±-Nepetalactone and 2E, 4E-nonadienal. While, phytol, caryophyllene oxide, E-caryophyllene, and thymol were the core compounds of essential in Polor population. The obtained results showed that environmental conditions are the important factors influencing the yield and also the chemical compositions of essential oils in N. fissa. Knowledge of the essential oil chemical composition in relation to ecological factors is a most prominent quality criterion for its marketing and contributes to its valorization as a functional ingredient in food industry.